A novel homozygous HES7 splicing variant causing spondylocostal dysostosis 4: a case report - Lv, Shaoguang; Wu, Yuanyuan; Liu, Fang; Jiao, Baoquan (Frontiers in Pediatrics, 2023)
Background: Spondylocostal dysostosis -4 (SCDO4) is characterized by short stature (mainly short trunk), dyspnea, brain meningocele, and recessive spina bifida occulta, which is caused by homozygous or compound heterozygous HES7 (Hhes family bHLH transcription factor 7) variantsmutations. The incidence of SCDO4 is remains unknown but the reported cases are extreme fewdue to the extremely low number of cases. The study was conducted to provideThis study reveals a novel homozygous pathogenic HES7 splicing variant causing SCDO4 and reviews all the published previously reported HES7 variantsmutations and corresponding symptoms, providing a comprehensively understanding overview of the phenotypes and genotypes of HES7 variants.We reported the case ofThis case report focuses on a Chinese neonate who was first hospitalized for tachypnea, cleft palate, and short trunk shortly. After a series of auxiliary examinations, the patient had was also found to have deformities of vertebrae and rib, left hydronephrosis, and patent foramen ovale. He underwent surgery for "congenital hydronephrosis" at 5 months old, and underwent cleft palate repair when he was 1 year old. After two and half years of follow-up, the boy developed normally. A novel homozygous HES7 splicing variant (c.226+1G>A, NM_001165967.2) was identified in the proband by whole-exome sequencing and verified by Sanger sequencing., which The variantmutation was inherited from bothhis parents respectively and verified by Sanger sequencing and. mMinigene assays demonstrated that this variant mutation would lead to the retainresulted in the retention of intron3 in the HES7 transcript. Including this case, a total of six HES7 mutations variants and thirteen patients with SCDO4 were have been reported.Our findings expand the genotype-phenotype knowledge of SCDO4 and provide new evidence for further genetic counselingcounselling.